Types of Therapeutic Laser Devices and their Medical Applications - Alwan, Emad Amer; Saadoun, Saadoun Hamoudi; mohy, Tuqa Riyadh; saad, Malak talib (American Journal of Botany and Bioengineering, 2024)
Laser devices are advanced tools characterized by their ability to achieve high precision in targeting tissues and providing treatment while minimizing damage to surrounding tissues. These devices are used in various medical specialties, such as ophthalmology, dentistry, general surgery, dermatology, and vascular surgery. Among the different types of therapeutic laser devices, we can mention the Carbon Dioxide (CO₂) laser, Argon laser, Neodymium-YAG (Nd :YAG) laser, Diode laser, Excimer laser, and Femtosecond laser. Their applications range from tumor removal and skin treatments to correcting visual defects and reducing joint pain. Benefits of Medical Laser: High precision: Reduces damage to surrounding tissues. Reduced bleeding: Contributes to reducing bleeding during surgeries. Faster recovery: Speeds up the healing and recovery process compared to traditional methods. Challenges: High cost of laser devices. The need for specialized training to ensure proper use. These devices represent a promising future in medicine, offering precise and non-invasive solutions across various medical fields.